The application of child adoption (balaku anak) and its legal effects on customary law system of the Dayak Ngaju tribe - Bramantyo, Rizki Yudha; Rahman, Irham (International research journal of management, IT and social sciences, 2020)
The purpose of this research is to find out how the application of children's behavior and its influence on the customary law system of the Dayak Ngaju Tribe. The research method used is qualitative. Primary data comes from observations and interviews. Meanwhile, secondary data from previous studies were collected to support the findings. The findings reveal that there are differences in the rule of law between Islamic law and positive law and customary law of the Dayak Ngaju tribe. Islamic law regulates inheritance and inheritance rights according to lineage, positive law regulates the return of cases of adoption to civil law, and customary Dayak Ngaju law recognizes adoption.